Mitochondrial Safeguard: a stress response that offsets extreme fusion and protects respiratory function via flickering‐induced Oma1 activation. (17th November 2020) - Murata, Daisuke; Yamada, Tatsuya; Tokuyama, Takeshi; Arai, Kenta; Quirós, Pedro M; López‐Otín, Carlos; Iijima, Miho; Sesaki, Hiromi
Abstract: The connectivity of mitochondria is regulated by a balance between fusion and division. Many human diseases are associated with excessive mitochondrial connectivity due to impaired Drp1, a dynamin‐related GTPase that mediates division. Here, we report a mitochondrial stress response, named mitochondrial safeguard, that adjusts the balance of fusion and division in response to increased mitochondrial connectivity. In cells lacking Drp1, mitochondria undergo hyperfusion. However, hyperfusion does not completely connect mitochondria because Opa1 and mitofusin 1, two other dynamin‐related GTPases that mediate fusion, become proteolytically inactivated. Pharmacological and genetic experiments show that the activity of Oma1, a metalloprotease that cleaves Opa1, is regulated by short pulses of the membrane depolarization without affecting the overall membrane potential in Drp1‐knockout cells. Re‐activation of Opa1 and Mitofusin 1 in Drp1‐knockout cells further connects mitochondria beyond hyperfusion, termed extreme fusion, leading to bioenergetic deficits. These findings reveal an unforeseen safeguard mechanism that prevents extreme fusion of mitochondria, thereby maintaining mitochondrial function when the balance is shifted to excessive connectivity. SYNOPSIS: The balance between membrane fusion and fission controls mitochondrial connectivity and function. Here, short pulses of membrane depolarization are found to drive an Oma1‐dependent stress response termed 'mitochondrial safeguard' that protects mitochondrial function upon increased mitochondrial connectivity. A mitochondrial stress response adjusts the balance between fusion and fission in response to increased mitochondrial connectivity in mammalian cells. Loss of mitochondrial GTPase Drp1 induces flickering, a repeated and transient decrease of mitochondrial membrane potential. Flickering partially activates the metalloprotease Oma1 and proteolytically inactivates Opa1 GTPase in Drp1‐knockout cells. Unless inactivated, Opa1 along with Mfn1 causes extreme mitochondrial fusion in Drp1‐knockuot cells. Extreme fusion of mitochondria leads to bioenergetic deficits. Abstract : Short pulses of membrane depolarization drive a mitochondrial stress response, named mitochondrial safeguard, that maintains mitochondrial function in response to excessive organelle connectivity.